Factors associated with health-related quality of life and financial toxicity among gynecological cancer patients in Southern Nigeria - Chibuzor F. Ogamba; Adedayo Joseph; Ayodeji Kayode Adefemi; Chidike Onyedikachi Ezegwui; Ajay Major; Rasaq Oluwagbemiga Jimoh; Michael Osahumen Orhue; Michael Chudi Ezeanochie; Boniface Uji Ago; Linda Ogochukwu Amah; Emeka Emmanuel Okoh; Courage Osamudiamen Idahor; et al. (Scientific Reports)
Abstract The health-related quality of life (HRQoL) and financial toxicity (FT) of women with gynecological cancers in sub-Saharan Africa have not been sufficiently explored. This study assessed predictors of HRQoL and FT, as well as the effect of FT on HRQoL, among affected women in Nigeria. This cross-sectional study investigated 574 women with gynecological cancers receiving care at various stages at five academic hospitals in southern Nigeria between June 2022 and September 2024. HRQoL and FT were evaluated using the FACT-G and FACIT-COST tools, respectively. Multivariable linear regression models estimated the associations of patient characteristics with HRQoL and FT and the effect of FT on HRQoL. Most women experienced FT. After multivariable adjustments, unemployed women, women with ovarian and uterine cancers and choriocarcinoma, higher disease stages, and worse ECOG status had worse HRQoL. Conversely, women in remission had better HRQoL. FT was worse with stages III and IV disease and in those on active treatment. However, older women, those with health insurance, higher income, ovarian cancer and choriocarcinoma had better FT. FT varied linearly with HRQoL, with better HRQoL per unit better FT. This effect was stronger in those with a first tumor, those in pre-treatment and those in remission. Our findings identify possible predictors of HRQoL and FT and suggest potential benefits of reducing FT on the HRQoL of women with gynecological cancers in Nigeria.